Preparation and growth mechanism of carbon nanotubes via catalytic pyrolysis of phenol resin. (August 2014) - Zhu, B. Q.; Wei, G. P.; Li, X. C.; Ma, Z.; Wei, Y.
Abstract : Using nickel nitrate as catalyst precursor, a cost effective method for large scale preparation of carbon nanotubes (CNTs) was investigated through catalytic pyrolysis of phenol resin in the temperature range of 600–1200°C under an Ar atmosphere. The morphology and structure of pyrolysed resin were characterised by X-ray diffraction, scanning electron microscope, transmission electron microscope and energy dispersive X-ray spectroscopy. The results show that the morphology and structure of CNTs depend on pyrolysis temperature, and the starting growth temperature of CNTs is ∼600°C. When the pyrolysis temperature is raised, the length and crystallinity of CNTs increase remarkably. High aspect ratio and well crystallised CNTs with average diameter of about 50–60 nm and micrometer scale length could be obtained at 1000°C. Scanning electron microscopy and transmission electron microscopy analysis reveals that the catalyst particle was located at the top of each CNT, which indicates the tip growth mechanism for CNTs. The growth process of CNTs will go through the following stages: decomposition of hydrocarbon components into the carbon atoms, dissolution, diffusion and segregation. The growth of CNTs agrees with vapour–solid (V-S) model.